WALKING IN FUNCTION OF MAIN FITNESS ACTIVITIES - Budimir Bijelić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
In motoricity a man is genetically "made" first to walk and just then in later stages to run, jump and perform other more complex motor activities. The intensive civilization development has a great negative influence on its basic mover-the man by taking him away from his natural, most basic need for walking. The hipokinesia has resulted in diseases common to a modern man such as putting on weight, cardiovascular disorders, diabetes, psycho-nerve tensions, respiration troubles, etc... Walking is one of major physical activities which in different states and/or ages serves as an adequate activity and moreover "remedy" for elimination of numerous disorders caused by urban civilization